2019
DOI: 10.3389/fimmu.2019.02949
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Bifidobacterium Administration on Experimental Autoimmune Myasthenia Gravis in Lewis Rats

Abstract: Beneficial effects of probiotics on gut microbiota homeostasis and inflammatory immune responses suggested the investigation of their potential clinical efficacy in experimental models of autoimmune diseases. Indeed, administration of two bifidobacteria and lactobacilli probiotic strains prevented disease manifestations in the Lewis rat model of Myasthenia Gravis (EAMG). Here, we demonstrate the clinical efficacy of therapeutic administration of vital bifidobacteria (i.e., from EAMG onset). The mechanisms invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…In this review, we provided examples of mechanistic ways microbes can alter disease pathology in IBD, SLE, RA, MS, and T1D models with microbes playing a role in pathology of additional autoimmune diseases (121)(122)(123)(124). While we focused on bacteria, emerging data suggests potential roles for yeast and enteric viruses in modulating immune responses and autoimmune and inflammatory disease (125)(126)(127)(128).…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we provided examples of mechanistic ways microbes can alter disease pathology in IBD, SLE, RA, MS, and T1D models with microbes playing a role in pathology of additional autoimmune diseases (121)(122)(123)(124). While we focused on bacteria, emerging data suggests potential roles for yeast and enteric viruses in modulating immune responses and autoimmune and inflammatory disease (125)(126)(127)(128).…”
Section: Resultsmentioning
confidence: 99%
“…A study with applications of two bifidobacteria or lactobacilli strains in a Lewis rat model also resulted in promising results ( 30 ). A subsequent study ( 134 ) reported the clinical efficacy of bifidobacterium on the course of EAMG and found that the immunomodulatory properties of viable bifidobacteria relied on the maintenance of the integrity of bacterial proteins and DNA sequences, which is denatured when exposed to high temperatures ( 135 ). Together, these studies support the effectiveness of probiotics in different immune-mediated inflammatory conditions and their possible use as a treatment in patients with MG to modulate the immune system and contribute to the restoration of the immunological tolerance to AChR.…”
Section: Potential Therapeutic Possibilitiesmentioning
confidence: 99%
“…Traditionally, various in vitro and in vivo models have been used to compare the immune regulatory roles of different bacterial strains. In vitro models include the macrophage RAW 264.7, human peripheral blood mononuclear cells (PBMCs), and bone-marrow-derived dendritic cells (BMDCs) [13][14][15]. Although these models are classically for primary immune evaluation, they have limitations.…”
Section: Introductionmentioning
confidence: 99%